2022
DOI: 10.1002/ieam.4565
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the water quality of urban tropical streams: An approach to daily variation in seasonality

Abstract: Using water quality indices (WQIs) is one way to monitor watercourses for water quality. Currently, there is a lack of information about their behavior in the diurnal cycle because sampling is often carried out in the morning. Also, few articles focus on assessing the urban impact on the spatial variability of WQIs in tropical first‐order streams. Such streams receive many pollutants varying in intensity according to population habits, justifying the possible diurnal variation in water quality in addition to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recently, there has been a great interest in refining water‐quality criteria in tropical regions because regions such as the NEA are prone to daily variation in weather, including high precipitation (Bega et al, 2021; Briciu et al, 2020; Nobre et al, 2020). Precipitation in the NEA region can range from 2800–4500 mm/year (INAMHI, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, there has been a great interest in refining water‐quality criteria in tropical regions because regions such as the NEA are prone to daily variation in weather, including high precipitation (Bega et al, 2021; Briciu et al, 2020; Nobre et al, 2020). Precipitation in the NEA region can range from 2800–4500 mm/year (INAMHI, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This could be improved in future studies in the NEA region by increasing the sampling throughout the year to include both the rainy and dry seasons. The need for better estimates of the water quality of watercourses has been recently reported (Bega et al, 2021; Briciu et al, 2020). For example, in a study assessing the variation in water quality variables in tropical first‐order urban streams in Brazil, the authors reported significant variation in water‐quality parameters throughout the day, resulting in distinct water‐quality classifications for the same stream (Bega et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its importance for Brazilian economic development (regional growth and income generation through jobs and better working conditions), the sugar-energy agro-industry has always had its image linked to environmental damage (Loarie et al, 2011;Zhang et al, 2015;Jaiswal et al, 2017;Monteiro et al, 2018;Zheng et al, 2022). In the past, water resources were used extensively by the sector and the final disposal of the effluents generated was carried out, in most cases, without proper control, which can negatively impact the receiving water courses (Bega et al, 2021;Bega et al, 2022;Ribeiro et al, 2022). However, in the 1990s, the sector began to worry about the sustainability of its production processes amid the competitive market that emerged, strategically shifting to a more organized production model (Santos, 2009).…”
Section: Introductionmentioning
confidence: 99%